Inhibitory effects of SARS-CoV-2 nonstructural proteins on the RIG-I signaling pathway - Reinholm, Arttu (My University, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) from the Coronaviridae family is an enveloped, spherical virus with a 30 kb long non-segmented positive single-stranded RNA genome, which encodes for 16 non-structural, four structural, and eleven accessory proteins. It was first discovered in 2019 in Wuhan, Hubei province, China, from a patient suffering from pneumonia caused by a previously unknown virus. SARS-CoV-2 rapidly spread throughout Wuhan, after which it spread around the world, leading to the current pandemic. The common symptoms caused by SARS-CoV-2 are fever, cough, dyspnea, and myalgia, similar to other human-infecting coronaviruses such as SARS-CoV and MERS-CoV, but less severe. SARS-CoV-2 has been shown to inhibit the RIG-I pathway, disrupting the production of type I and III interferons, and to evade host innate immune response. In this study, I analyzed whether some SARS-CoV-2 proteins have an ability to inhibit the production of type III interferon by interfering with the RIG-I pathway. Additionally, I checked if the ORF9B accessory protein was immunogenic. To accomplish this, I cloned the genes of interest into mammalian expression vectors, which were then transfected to HEK-293 cells along with a constitutively active form of RIG-I and IFN-1 promoter luciferase reporter plasmid. Structural proteins were incapable of inhibiting RIG-I induced activation of type III interferon promoter, while nonstructural proteins Nsp1, Nsp6, and Nsp13 showed clear inhibitory activity. ORF9B was found not to be immunogenic.
Keywords: RIG-I, SARS-CoV-2, nonstructural protein, luciferase, western blotting, interferon